PENINGKATAN SKILL SISWA TUNARUNGU MELALUI PELATIHAN PATCHWORK DAN QUILTING BERBASIS APLIKASI SIGN TALK DI SLB-B YPAC PALEMBANG - Anita Desiani; Bambang Suprihatin; Ali Amran; Yadi Oktariansyah; Siti Rusdiana Puspa Dewi; Jonatan Jonatan; Slamet Prayogo; Lonamonika Sinabutar (Jurnal AbdiMas Nusa Mandiri, 2026)
Skill development for deaf students at SLB-B YPAC Palembang still faces significant challenges, particularly due to communication barriers between teachers and students that hinder knowledge transfer. This community service program aims to enhance hard skills (technical sewing skills in patchwork and quilting) as well as soft skills (communication, teamwork, and independence) through the integration of an Artificial Intelligence (AI)-based application called Sign Talk. The implementation method was carried out through a workshop and intensive mentoring scheme over 4 months, which included 3 main training sessions, each lasting 120 minutes, for 15 deaf students. Evaluation was conducted using pre-test and post-test instruments analyzed descriptively. The results of the activity showed an increase in students’ soft skills of 40.5%. For hard skills, specifically sewing competencies, there was a 23.31% increase. Although 90% of participants rated the Sign Talk application as very helpful in understanding instructions during the activity, further development of the Sign Talk vocabulary is needed. Additionally, this activity can be expanded to include other hard skill trainings with Sign Talk serving as the communication medium.